Physiological and Oxidative Responses of Japanese Mint Grown Under Limited Water and Nitrogen Supplies in an Evaporated Greenhouse System - Sommano, Sarana Rose; Kanthawang, Naruemon; Janpen, Chananchida; Norkum ai, Pasin; Wongkaew, Malaiporn; Inkham, Chaiartid; Van Doan, Hien; Cheewangkoon, Ratchadawan (Frontiers in Sustainable Food Systems, 2022)
Within this study, influences of abiotic factors inducing biomass and synthesis of secondary metabolites in Japanese mint (Mentha arvensis) were studied. Plants were cultivated in the evaporate greenhouse system under 50% shading, at temperature at 25 – 28 °C and with relative humidity at 60 – 65 %. After planting at 12 weeks, the result showed that water management at 75% and 100% evaporate transpiration crops (ETc) gave the highest growth measures namely; plant height (ca. 22.96 cm), number of stem (ca. 7.75 stems), stem thickness (ca. 3.69 mm), diameter of canopy (ca. 28.03 cm), number of leaves per plant (ca. 151.28 leaves), fresh weight (ca. 108.07 g) and dry weight (ca. 22.29 g). While, leaf area value (1104.10 cm2) was the highest at 75% water and the highest SPAD value was at 25% (41.13 SPAD unit). Levels of secondary metabolite as potential of antioxidant by DPPH and ABTS methods had no significant difference, however, total flavonoid was higher in ETc 25% and 50% as compared to other treatments (ca. 0.41 mg gallic acid/g sample). The content of menthol was well correspondent with biomass yield. In the second experiment, nitrogen level at 210 and 310 mg/L gave the highest in growth measures namely; plant height (ca. 21.41 cm) and SPAD unit (ca. 25.54 SPAD unit). In addition, the nitrogen level at 310 mg/L gave the highest in growth measures viz; number of stem (9.00 stems), stem thickness (3.28 mm), diameter of canopy (27.55 cm), number of leaves per plant (162.57 leaves), leaf area (568.38 cm2), fresh weight (80.79 g) and dry weight (17.09 g). At 12 weeks of cultivation, the highest level of secondary metabolites as described by total phenolic and flavonoid and menthol were achieved when higher rate of nitrogen was applied. The results advised that Japanese mints were well adjusted to the stresses in the controlled atmospheric humidity of the greenhouse and nitrogen was key important element for increasing the productivity.